Case Study: Izmit Domestic and Industrial Water Supply Build-Operate-Transfer Project - Şentürk, H. A.; Kaplanoğlu, S. B.; YAZICI, GÖKHAN (ASCE-AMER SOC CIVIL ENGINEERS, 1801 ALEXANDER BELL DR, RESTON, VA 20191-4400 USA, 2004)
The "build, operate, and transfer model" (BOT) is a financing model, which is used in many developing countries to finance new infrastructure projects with private sector participation. The BOT method foresees the financing, designing, building, operating, and managing of the facility by the private sector and then its transfer free of charge, to the owner after a predetermined concession period. For interested parties, the history of BOT laws and projects in Turkey is presented as an Appendix. In this study, the Izmit Domestic and Industrial Water Supply Project, the biggest privately financed water Supply project procured under the BOT model in the world at the time and the first in Turkey will be introduced and the problems that arose during the implementation of the project, namely, the scope of the project, equity debt ratio, return on equity, principles of accounting, coordination of State departments, land access, determination of the optimum operation period, and the sale price of the water, will be presented and suggestions will be given on how to deal with these problems.
Keywords: build/operate/transfer; Water Supply; Project Management; Turkey; Case Reports; İnşa / işletmek / transfer; Su Tedarik Etmek; Proje Yönetimi; Türkiye; Vaka Raporları